Egrang Traditional Game: Cultural Literacy in Elementary School Social Studies - Anisa Putri Mulyaningsih; Nurdiansyah Nurdiansyah; Jennyta Caturiasari (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to analyze the role of the traditional egrang game in fostering cultural literacy in elementary school students, particularly those related to the values ​​of cooperation, cultural identity, diversity, and awareness of preserving local cultural heritage in the context of social studies learning. Methodology: The study used a descriptive qualitative approach. Subjects were selected purposively, involving fifth-grade students, extracurricular teachers, social studies teachers, and the principal at an elementary school in Purwakarta. Data collection was conducted through participant observation, semi-structured interviews, and field documentation. Data analysis used the Miles and Huberman interactive model with source triangulation to ensure the credibility of the findings. Main Findings: Egrang have been shown to foster three dimensions of students' cultural literacy: (1) recognition of local culture with a Very good score on the identification of egrang as a traditional heritage and part of regional cultural identity; (2) understanding of the values ​​of cooperation, hard work, and diversity that emerged organically during the game without explicit instruction; (3) the highest cultural awareness, characterized by students' enthusiasm and willingness to pass on egrang to the next generation. Novelty/Originality of this study: This research is the first to specifically integrate egrang into a cultural literacy framework within the context of elementary school social studies education. Unlike previous studies that focused on motor skills or general character, this study offers a new perspective on egrang potential as a contextual and meaningful medium for social studies learning based on local culture.